2020
DOI: 10.1103/physrevb.102.134426
|View full text |Cite
|
Sign up to set email alerts
|

Strong magnetocaloric effect induced by spin reorientation transitions in epitaxial Ho thin films

Abstract: Magnetocaloric effect (MCE) in antiferromagnetic holmium (Ho) film is studied near the spin reorientation temperatures. A series of magnetization isotherms from 60 K to 150 K around the Neel temperature, T N ≈ 130 K were recorded for both in-plane and out-of-plane magnetic field orientations. A change in entropy, ∆S M of-5 J/kg K was found near T N for an in-plane field orientation. A large change in ∆S M of-11.8 J/kg K due to a fan-helix spin transition at Т = 90 K is observed for an in-plane field orientatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…There has been growing interest in the study of rare-earth nanostructures, which was initiated by finding a number of novel effects, such as the giant magnetocaloric effect [8]. Such effects are determined by the magnetic properties of nanostructures and their variations with temperature or magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…There has been growing interest in the study of rare-earth nanostructures, which was initiated by finding a number of novel effects, such as the giant magnetocaloric effect [8]. Such effects are determined by the magnetic properties of nanostructures and their variations with temperature or magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, stationary spin states of Ho are the focus of researchers. All these states are well-known in the literature [1][2][3][4][5][6][9][10][11][12]. Variations in thicknesses and mechanical strains cause a significant change in the spin state map presented in field-temperature coordinates.…”
Section: Introductionmentioning
confidence: 83%
“…A neutron diffraction study indicated that a film with a thickness of approximately 100 nm exhibits properties distinct from those of the bulk material, yet remains suitable for examining the periodicity of a spin helix and various incommensurate spin structures [2]. X-ray diffraction (XRD) was recorded to confirm the hexagonal structure and orientation of the c axis [3].…”
Section: Experimental Techniques and Samplementioning
confidence: 99%
See 2 more Smart Citations